Immunogenicity of BNT162b2 vaccine against the Alpha and Delta variants in immunocompromised patients with systemic inflammatory diseases. Issue 5 (12th January 2022) - Hadjadj, Jerome; Planas, Delphine; Ouedrani, Amani; Buffier, Solene; Delage, Laure; Nguyen, Yann; Bruel, Timothée; Stolzenberg, Marie-Claude; Staropoli, Isabelle; Ermak, Natalia; Macraigne, Laure; Morbieu, Caroline; et al.
Abstract : Objectives: The emergence of strains of SARS-CoV-2 exhibiting increase viral fitness and immune escape potential, such as the Delta variant (B.1.617.2), raises concerns in immunocompromised patients. We aimed to evaluate seroconversion, cross-neutralisation and T-cell responses induced by BNT162b2 in immunocompromised patients with systemic inflammatory diseases. Methods: Prospective monocentric study including patients with systemic inflammatory diseases and healthcare immunocompetent workers as controls. Primary endpoints were anti-spike antibodies levels and cross-neutralisation of Alpha and Delta variants after BNT162b2 vaccine. Secondary endpoints were T-cell responses, breakthrough infections and safety. Results: Sixty-four cases and 21 controls not previously infected with SARS-CoV-2 were analysed. Kinetics of anti-spike IgG after BNT162b2 vaccine showed lower and delayed induction in cases, more pronounced with rituximab. Administration of two doses of BNT162b2 generated a neutralising response against Alpha and Delta in 100% of controls, while sera from only one of rituximab-treated patients neutralised Alpha (5%) and none Delta. Other therapeutic regimens induced a partial neutralising activity against Alpha, even lower against Delta. All controls and cases except those treated with methotrexate mounted a SARS-CoV-2 specific T-cell response. Methotrexate abrogated T-cell responses after one dose and dramatically impaired T-cell responses after two doses of BNT162b2. Third dose of vaccine improved immunogenicity in patients with low responses. Conclusion: Rituximab and methotrexate differentially impact the immunogenicity of BNT162b2, by impairing B-cell and T-cell responses, respectively. Delta fully escapes the humoral response of individuals treated with rituximab. These findings support efforts to improve BNT162b2 immunogenicity in immunocompromised individuals (ClinicalTrials.gov number, NCT04870411 ).